Conserved linkage between the puffer fish (Fugu rubripes) and human genes for platelet-derived growth factor receptor and macrophage colony-stimulating factor receptor. - How, G F; Venkatesh, B; Brenner, S (Genome Research, 1996)
We have cloned and sequenced the teleost homologs of the human genes encoding platelet-derived growth factor receptor-beta (PDGFR beta) and macrophage colony-stimulating factor 1 receptor (CSFIR) from the puffer fish Fugu rubripes. The Fugu PDGFR beta and CSFIR genes each consist of 21 coding exons similar to the human CSFI gene, but are considerably smaller than their human counterparts because of the smaller introns. Furthermore, the two Fugu genes are linked tandemly in a head-to-tail array similar to their human homologs with 2.2 kb of intergenic sequence. Amino acid sequences of the Fugu and human PDGFR beta and CSFIR genes show an overall homology of 45% and 39%, respectively, with the kinase domains showing a much higher degree of conservation. Dot-matrix analysis revealed several short stretches of conserved sequences in the 3' untranslated regions of the PDGFR beta genes and the adjacent promoter regions of the CSFIR genes. These conserved sequences may have a role in the regulation of expression of either or both of these closely linked genes.